2021
DOI: 10.3390/jcm10122659
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Chronic Heart Failure on Retinal Vessel Density Assessed by Optical Coherence Tomography Angiography in Children with Dilated Cardiomyopathy

Abstract: (1) Introduction: The aim of this study is to assess retinal vessel density (VD) in the superficial capillary plexus layer (SP) and deep capillary plexus layer (DP) in children with chronic heart failure (CHF) in the course of dilated cardiomyopathy (DCM) using optical coherence tomography angiography (OCTA). (2) Methods: Thirty children with CHF due to DCM lasting more than six months, with an enlarged left ventricle and impaired left ventricular systolic function (left ventricular ejection fraction (LVEF) ≤ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 66 publications
(107 reference statements)
1
12
0
Order By: Relevance
“…Why the association between adverse markers of cardiac remodeling and superficial but not deep retinal vessels is not established and open to speculation. A recent OCTA study by Rakusiewicz 51 reported similar OCTA findings, where there was a significantly altered vessel density in the superficial capillary plexus but not the deep capillary plexus in children with chronic heart failure because of dilated cardiomyopathy as compared with healthy children. However, Wang 52 observed changes in the vessel densities in both superficial and deep plexuses in patients with chronic heart failure versus those without it.…”
Section: Discussionmentioning
confidence: 59%
“…Why the association between adverse markers of cardiac remodeling and superficial but not deep retinal vessels is not established and open to speculation. A recent OCTA study by Rakusiewicz 51 reported similar OCTA findings, where there was a significantly altered vessel density in the superficial capillary plexus but not the deep capillary plexus in children with chronic heart failure because of dilated cardiomyopathy as compared with healthy children. However, Wang 52 observed changes in the vessel densities in both superficial and deep plexuses in patients with chronic heart failure versus those without it.…”
Section: Discussionmentioning
confidence: 59%
“…Different from the current clinical use of brain natriuretic peptide, chest X-ray, color Doppler echocardiography, and patient signs, this study evaluates patients' circulatory hyperemia by remotely monitoring the 24-hour average heart rate, resting heart rate, and patient activity. Several studies have confirmed the safety and effectiveness of remote monitoring of the 24-hour average heart rate and other parameters [ 26 , 27 ]. Some scholars have pointed out that the increase of the 24-hour average heart rate, heart rate variability, and the decrease of patient activity could reflect the clinical status of patients and predict heart failure decompensation events [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it is found that the readmission rate of patients with heart failure can be reduced by remote monitoring of a 24-hour average heart rate, resting heart rate, patient activities, other parameters, and early corrections of abnormal parameters [ 26 ]. Further analysis has found that there was no significant difference in the readmission rate of heart failure in patients with grade NYHAII, but for patients with grade NYHAIII, the readmission rate in the study group was lower compared to that in the control group, which was consistent with our expectations [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the ability to examine the choroidal layers with swept source or EDI-OCT offers new research opportunities for patients with HFrEF and the ischemic type of HFrEF, which is the leading cause of LV dysfunction in adults worldwide. [16][17][18][19] SFCT is commonly used in research trials. Still, it re ects only the whole choroidal structure and may be affected by various factors such as age, axial length, intraocular pressure, and systolic blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 The results of the current study are in accordance with previous studies on patients with HFrEF in terms of reduced retinal VD in comparison with the normal population. 19,49 Since the blood supply to the retina is physiologically kept constant by speci c autoregulation mechanisms, such a decrease in VD in patients with chronic HF can also be justi ed by insu ciency to autoregulate the retinal blood supply in these patients. 19 The main advantage of our study is its use of a noninvasive technology that enables the reproducible and quantitative evaluation of abnormalities in the retinal and choroidal microvasculature in a homogeneous group of patients with HFrEF.…”
Section: Discussionmentioning
confidence: 99%